Fusion pore in exocytosis: More than an exit gate? A β-cell perspective. (December 2017) - Hastoy, Benoit; Clark, Anne; Rorsman, Patrik; Lang, Jochen
Graphical abstract: Highlights: Exocytosis requires structural dynamics and mobility of SNARE protein transmembrane domains. SNARE transmembrane domains closely interact with and shape lipids. The transmembrane domains play an active role in pore opening and expansion. Diabetes may influence exocytosis via membrane lipid composition and protein expression. Subtle changes in diabetes may become clinically relevant by their life-long nature. Abstract: Secretory vesicle exocytosis is a fundamental biological event and the process by which hormones (like insulin) are released into the blood. Considerable progress has been made in understanding this precisely orchestrated sequence of events from secretory vesicle docked at the cell membrane, hemifusion, to the opening of a membrane fusion pore. The exact biophysical and physiological regulation of these events implies a close interaction between membrane proteins and lipids in a confined space and constrained geometry to ensure appropriate delivery of cargo. We consider some of the still open questions such as the nature of the initiation of the fusion pore, the structure and the role of theS olubleN -ethylmaleimide-sensitive-factorA ttachment proteinRE ceptor (SNARE) transmembrane domains and their influence on the dynamics and regulation of exocytosis. We discuss how the membrane composition and protein-lipid interactions influence the likelihood of the nascent fusion pore forming. We relate these factors to the hypothesis that fusion pore expansion could be affected in type-2 diabetes via changes in disease-related gene transcription and alterations in the circulating lipid profile. Detailed characterisation of the dynamics of the fusion pore in vitro will contribute to understanding the larger issue of insulin secretory defects in diabetes.